Toward a gathering place: Le Corbusier’s city after World War II - Sequeira, Marta (2016)
The public spaces in Le Corbusier’s plans are usually considered to break with the past and to have nothing whatsoever in common with the public spaces created before modernism. This is view is fostered by evidence that highlights their innovative character, and also by misinterpretations of some of Le Corbusier’s own observations and liberal use of words like civilisation machiniste [‘machine civilization’], l’esprit nouveau [‘new spirit’] and l’architecture de demain [‘architecture of tomorrow’], which mask any evocation of the past. However, if we manage to rid ourselves of certain preconceived ideas, which underpin a somewhat less-than-objective idea of modernity, we " nd that Le Corbusier’s public spaces not only fail to break with the historical past in any abrupt way but actually testify to the continuity of human creation over time. ! is is what this article aims to demonstrate through a careful analysis of two of Le Corbusier’s public spaces dating from the period immediately after the Second World War.